Covid19: Efektivitas Kelas Virtual bagi Siswa Sekolah Dasar di Desa - Nurhasanah Walijah Walijah (Jurnal Ilmu Pendidikan, 2025)
As of March 2020, Coronavirus Disease 2019 (COVID-19) reached Indonesia. From that point on, life in Indonesia changed, and public activities were suspended to prevent the spread of COVID-19. The decision by the Ministry of Education and Culture (Kemendikbud) to shift learning from in-person to virtual settings required teachers and students to adapt. In other countries and certain regions of Indonesia, this virtual learning method is not unfamiliar. However, it is a novelty, particularly in rural villages. With the emergence of this new learning method, stakeholders did not merely offer advice or issue orders to the community. Instead, they are providing efforts and solutions to address the shortcomings and ensure the sustainability of distance learning. By applying Fazlur Rahman’s theory of multiculturalism, it is hoped that developments in the field of education—particularly during this pandemic—will become even more innovative and creative. Additionally, a sociological approach is needed.